Extending Educational Reform - Datnow, Amanda (Taylor & Francis, 2002)
In an effort to improve student achievement, thousands of US schools have adopted school reform models devised externally by universities and other organizations. Such models have been successful in improving individual schools or groups of schools, but what happens when educational reform attempts to extend from one school to many? Through qualitative data from several studies, this book explores what happens when school reform 'goes to scale'. Topics covered include: *why and how schools are adopting reforms *the influence of the local context and wider constraints on the implementation of reform *teachers and principals as change agents in schools *the evolution of reform design teams *the implementation, sustainability and expiration of reform, and its impact on educational change Each chapter concludes with guidelines for policy and practice. This book will be of interest to educational leaders and staff developers, educational researchers and policy makers, in the US and internationally.